Guidelines for Occupational Health and Radiation Safety In Catheterization Laboratory - ชีวะประเสริฐ, อภิเดช; เจียมจรัสรังษี, วิโรจน์ (Journal of Preventive Medicine Association of Thailand, 2018)
Due to the recently growing number of patients with heart disease and the accompanying medical care requirement, the number of catheterization laboratories in public hospitals in Thailand rose from 20 to 36 in just six years. At the same time, the proportion of medical radiation overdose incidents among people receiving massive dose of radiation from Digital Fluoroscopy had increased almost three times in the past ten years. The crucial reason is that guidelines for proper use of radiation are insufficient and inadequate, including the ambiguity of catheterization laboratory specific standards. Consequently, development of occupational health and radiation safety in catheterization laboratory guidelines is necessary